A rare anomaly of left renal vein drainage into the left common iliac vein: A case report. (2016) - Kawai, Kazushige; Tanaka, Toshiaki; Watanabe, Toshiaki
Highlights: We report a rare anomaly of the left renal vein in a sigmoid colon cancer patient. We identified the variation before surgery by CT-angiography. By identifying the anomaly, the laparoscopic colon surgery was performed safely. Abstract: Introduction: Herein, we describe a case of sigmoid colon cancer with a rare anomaly of the left renal vein located between the inferior mesenteric artery (IMA) and the left common iliac artery. Case presentation: A 57-year-old woman with sigmoid colon cancer underwent three-dimensional computed tomography angiography for a preoperative assessment; the results revealed a rare variant of the left renal vein. There were two left renal veins: one retroaortically drained into the inferior vena cava, and the other was located between the IMA and the left common iliac artery and drained into the left common iliac vein. Laparoscopic sigmoid colectomy was performed safely while carefully avoiding any injury to the left renal vein located posterior to the IMA. Discussion: Several variations of the left renal vein have been reported, such as retroaortic or circumaortic left renal veins. The variants of renal vessels, which are frequently overlooked in the preoperative assessment, is rarely affected in colorectal surgery. However, if the surgeon is unaware of such renal vessel anomalies, an injury can occur, resulting in severe bleeding. Conclusion: It is important that surgeons identify retroperitoneal vessel variants before performing colorectal surgery.